Spiritual assessment in healthcare practice - McSherry, Wilfred; Ross, Linda (M & K, 2010)
There has been a groundswell of interest in and recognition of the importance the spiritual part of a person's life has to play in coping with/recovery from illness as well as in the attainment and maintenance of health, wellbeing and quality of life. Addressing the spiritual part of life is now a key part of the health care professional's job but this raises the question of how this part of life can be assessed and catered for and how health care professionals might be equipped for this task. Wilf McSherry and Linda Ross's new edited text tackles this very issue with contributors from different disciplines (including nursing, medicine, theology and chaplaincy) and countries (UK, USA, Malta) offering their own perspectives on this important part of care. Each chapter, therefore, has its own unique style but is concerned with one outcome, to see spiritual assessment and care as an integral part of holistic care whatever the setting.